Dietary habits of shooting athletes - Jakus, Tadeja (Annales kinesiologiae (Koper), 2024)
Purpose: Shooting is a sport in which dietary habits and the timing of meals is not often represented. The aim of this paper is to compare the dietary habits, timing of meals and training frequency of Slovenian and foreign athletes. Methods: The sample included 88 shooter athletes (35 Slovenian and 53 foreign athletes), aged 14 to 60, who participate in competitions. Data by dietary habits, diet, training and BMI were collected via a questionnaire. Results: Athletes train and compete most frequently using an air rifle. Foreign athletes train more often and spend more time training than Slovenian athletes (p < 0.001). The average BMI was 24.9 ± 4.9 kg/m2 and was higher in athletes who competed at national level (26.8 ± 5.6 kg/m2) compared to international level (23.0 ± 3.1 kg/ m2) (p = 0.022). We found a difference between the groups in lunch (p = 0.041), morning (p = 0.020) and evening (p = 0.008) snacks. Slovenian athletes reached for food during training less frequently than foreign athletes (p = 0.007). More than half of the athletes (p < 0.001). Conclusions -athletes tend to train more frequently, have better nutritional planning and eat more meals after training than their Slovenian counterparts.
Keywords: eating behaviour; nutrition; prehrana; prehranske navade; shooting; strelstvo